KEWAJIBAN MEDIASI SEBELUM GUGATAN GANTI RUGI PERDATA ATAS PELANGGARAN HAK CIPTA DI INDONESIA - Mayesha Andriana Yasmine (Repertorium: Jurnal Ilmiah Hukum Kenotariatan, 2021)
Copyright is the exclusive right of the creator that appears automatically based on declarative principles. As one part of Intellectual Property Rights which has the widest scope of protected objects, copyright plays a major role in the development of the creative economy in Indonesia. However, there are problems with copyright regulations in Indonesia, namely Law Number 28 of 2014 concerning Copyright. The problem in question is contained in  Article 95 paragraph 1, the norm in that article is not appropriate because it is "regulating" (aanfullen) marked by the word "can" (dapay), while the norm in Article 95 paragraph 4 is "forced" (dwingen) marked by the word "must" (harus), the imbalance results in the non-binding of Alternative Dispute Resolution (ADR) and creates legal uncertainty for resolution of copyright disputes. Departing from this, this research purpose to determine appropriate efforts to solve the problem and the basis or supporting factors for these efforts. In addition to research purposes, this research also has uses consisting of theoretical and practical uses. Regarding the research method, the approach applied is normative juridical. Then the specification of this research is descriptive analytical. Regarding data, the collection technique applied is document study and the analytical method applied is normative qualitative. The results of this research, based on the principle of legal certainty, simple, quick, low-cost court principle, the legal theory of development, theories of the welfare state and the theory of economic analysis of law, the appropriate effort to overcome the problems in this research is to change the nature of norms in Article 95 Paragraph 1, by requiring mediation before filing a lawsuit for civil compensation in copyright disputes.